The Effect Of Using Picture Series On Students Reading Comprehension Of Narrative Texts - Favorita, Hepy New Islamy; Astutik , Indri; Hatip, Mochamad (Universitas Muhammadiyah Jember, 2023)
It is obvious that students face difficulties in understanding words and identifying story elements when reading narrative texts. Moreover, they often exhibit disinterest, boredom, passivity, and reluctant to participate in reading class activities. One of the effective teaching methods that can be employed to address this issue is the use of picture series. The objective of this study was to determine the level of impact that picture series have on students' reading comprehension in narrative text. A quantitative approach of quasi experimental design was employed to analyze the data collected from the study's results. The study involved a total of 64 students who were divided into two groups: an experimental group consisting of 32 participants who were taught narrative texts using picture series, and a control group of 32 participants who were taught using a textbook. The data collected from the study were analyzed using SPSS to determine if there was a significant impact on students' reading comprehension when picture series were utilized. The results of the independent sample t-test showed a significant value (2-tailed) of 0.01, which was lower than the significance level of 0.05 (0.01 < 0.05). Consequently, it was concluded that the alternative hypothesis, which stated that there was a significant effect of using picture series on students' reading achievement, was supported. This suggests that the use of picture series had a notable influence on students' reading achievement when learning narrative texts.